Programming — A New Form of Art in the Modern Era - To‘rayeva , Madina (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article explores the creative and innovative nature of programming in the context of modern information technology transformation. The main objective of the study is to analyze programming not merely as a technical tool, but as a fundamental phenomenon that shapes digital art and systematic thinking. Based on the cognitive approaches of Jan Sebastian Zipp, the article highlights the concept of creativity in the field of information technology and its impact on the methodology of teaching computer science. The author substantiates the pedagogical advantages of project-based learning (PBL) and the development of algorithmic thinking in computer science education. The research findings indicate that perceiving programming as an art increases students’ intrinsic motivation and prepares them for innovative activities. The results of the study can be used by computer science teachers and educational methodologists.